2012
DOI: 10.1364/oe.20.003296
|View full text |Cite
|
Sign up to set email alerts
|

1-kilowatt CW all-fiber laser oscillator pumped with wavelength-beam-combined diode stacks

Abstract: We have demonstrated a monolithic cladding-pumped ytterbium-doped single all-fiber laser oscillator generating 1 kW of CW signal power at 1080 nm with 71% slope efficiency and near diffraction-limited beam quality. Fiber components were highly integrated on "spliceless" passive fibers to promote laser efficiency and alleviate non-linear effects. The laser was pumped through a 7:1 pump combiner with seven 200-W 91x nm fiber-pigtailed wavelength-beam-combined diode-stack modules. The signal power of such a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 9 publications
0
41
0
2
Order By: Relevance
“…Schematic of SBC with external cavity feedback based on grating 由图 1 可见, 光谱合束装置是由半导体激光器阵列(DLA)、 快轴准直镜(FAC)、 慢轴准直镜(SAC)变换柱 透镜、 光栅与外腔镜组成。半导体激光器的大发散角, 会严重限制了半导体激光器阵列和叠阵的光谱合束, 原因在于慢轴光束的发散, 使得每个阵列单元之间形成交叉耦合, 这种交叉耦合导致多旁瓣输出 [10] [12] 国波茨坦大学和丹麦技术大学提出了一种基于离轴反馈的光谱合束方法 [16][17] 2009 年丹麦技术大学 Vijayakumar [18] 等利用图 7(a)所示的旁轴反馈对高功率宽发射面半导体激光器线…”
Section: -unclassified
“…Schematic of SBC with external cavity feedback based on grating 由图 1 可见, 光谱合束装置是由半导体激光器阵列(DLA)、 快轴准直镜(FAC)、 慢轴准直镜(SAC)变换柱 透镜、 光栅与外腔镜组成。半导体激光器的大发散角, 会严重限制了半导体激光器阵列和叠阵的光谱合束, 原因在于慢轴光束的发散, 使得每个阵列单元之间形成交叉耦合, 这种交叉耦合导致多旁瓣输出 [10] [12] 国波茨坦大学和丹麦技术大学提出了一种基于离轴反馈的光谱合束方法 [16][17] 2009 年丹麦技术大学 Vijayakumar [18] 等利用图 7(a)所示的旁轴反馈对高功率宽发射面半导体激光器线…”
Section: -unclassified
“…Benefit from the fiber geometry, fiber lasers are now associated with high average power, excellent beam quality, easy thermal management, superior reliability, and compact size [1,2]. All of these outstanding characteristics make them an ideal source for many industrial and scientific applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first kilowatt-level near diffraction-limited fiber laser was established in 2004 [3], a 10 kW level single-mode fiber laser has been accomplished by the IPG with tandem pumping technology [4]. For the direct diode-pumped case, most of the reported single-mode fiber lasers produce limited output power of 1-2 kW level [1,[5][6][7][8][9]. Most recently, one 2.5 kW all-fiber master oscillator power amplifier (MOPA) pumped by 976 nm laser diodes (LDs) has been demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the matured large mode area (LMA) FBG inscription techniques [10][11][12] , the output powers of the monolithic fiber laser oscillator have increased remarkably during the last years. In 2012, a monolithic fiber laser oscillator with output power of ∼1 kW was reported based on ytterbium-doped fiber (YDF) with a core/inner-cladding diameter of 20/400 μm and 915 nm laser diodes (LDs) [13] . Later in 2014, Yu et al of our group reported a 1.5 kW monolithic fiber laser oscillator in a similar scheme [14] .…”
mentioning
confidence: 99%
“…Theoretically, it is a most effective technique to mitigate the SRS by increasing the mode area of the high-power fiber lasers [16,17] . In consideration of the LMA FBG manufacture techniques, most reported high-power monolithic fiber laser oscillators employed gain fiber with a core/inner-cladding diameter of 20/400 μm and corresponding FBGs, which are commercially available and ensure a near-diffraction-limited beam quality [13][14][15]18,19] . However, as the output power gradually increases, the fiber laser oscillators based on gain fiber with core diameter of ∼20 μm face severe limitation of SRS in the power scaling [14,15] .…”
mentioning
confidence: 99%